Search for a light pseudoscalar Higgs boson in the boosted mu mu tau tau final state in proton-proton collisions at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Bergauer,T; Dragicevic,M; Ero,J; Del,Valle AE; Flechl,M; Fruhwirth,R; Jeitler,M; Kratschmer,I; et al. (The Journal of High Energy Physics, 2020)
A search for a light pseudoscalar Higgs boson (a) decaying from the 125 GeV (or a heavier) scalar Higgs boson (H) is performed using the 2016 LHC proton-proton collision data at s√ = 13 TeV, corresponding to an integrated luminosity of 35.9 fb−1, collected by the CMS experiment. The analysis considers gluon fusion and vector boson fusion production of the H, followed by the decay H → aa → μμττ, and considers pseudoscalar masses in the range 3.6 < ma < 21 GeV. Because of the large mass difference between the H and the a bosons and the small masses of the a boson decay products, both the μμ and the ττ pairs have high Lorentz boost and are collimated. The ττ reconstruction efficiency is increased by modifying the standard technique for hadronic τ lepton decay reconstruction to account for a nearby muon. No significant signal is observed. Model-independent limits are set at 95% confidence level, as a function of ma, on the branching fraction () for H → aa → μμττ, down to 1.5 (2.0) × 10−4 for mH = 125 (300) GeV. Model-dependent limits on (H → aa) are set within the context of two Higgs doublets plus singlet models, with the most stringent results obtained for Type-III models. These results extend current LHC searches for heavier a bosons that decay to resolved lepton pairs and provide the first such bounds for an H boson with a mass above 125 GeV.